Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - De la Torre Garro, Angela Ysabel (2019)
Camposol is an agro-export company of Peruvian origin that was created more than 20 years ago, has a strong reputation and great experience for the important client portfolio they have. It is characterized by offering high quality products and volume which allows it not only to export to important international markets but also to market directly with retailers, which is considered its most important channel. Its product portfolio consists of avocados, seafood, blueberries, grapes and mangoes. It currently has offices in foreign countries, as is the case in Europe, the United States and Asia, which allows it to have a better response to the client, a better knowledge and adaptation to the culture, in order to take advantage of the market opportunities. During the case analysis, the opportunities and threats of the current international market are evaluated and what strategies could be used so that Camposol can grow and is projected to be a leader in its product lines.